THE PRESENTATION OF THE LEARNING MATERIALS DEPICTING CHARACTER EDUCATION VALUES IN THE ELT TEXTBOOK FOR JUNIOR HIGH SCHOOL STUDENTS: A CONTENT ANALYSIS - Pratiwi, Yasshinta Ika; Sukmaantara, I Putu; Andayani T, Made Adi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
In education, the issue of character education has been considered necessary in developing students’ character. Furthermore, English Language Teaching (ELT) should teach students character education values in the textbook and its materials. This research aimed to investigate the learning materials depicting character education values presented or not in the textbook. The learning materials in this research were analysed, both visual and verbal materials depictions. This research was designed as a content analysis because it described the analysis of character education values found in the textbook. The research results of a content analysis revealed that to analyse the five core character education values covered in the textbook, specifically in semester 2. However, it was not all of them found in each chapter. The textbook only presented the character education values of nationalism, independence, mutual cooperation, and integrity, except religiosity with 15 data in total. The results imply that this research was necessary to provide opportunities to the textbook’s authors, English teachers, and future researchers that it was essential for them to deliver character development to students in the education context.